(untitled) (Oratio Directa, 2021)
This conceptual study examines symbolic violence in television content and its implications for children's attitudes and behavior. The analysis integrates four perspectives: Pierre Bourdieu's symbolic violence, Peter L. Berger and Thomas Luckmann's social construction of reality, Karen Horney's personality anxiety, and George Gerbner's cultivation theory. Symbolic violence operates through unequal communication relations that normalize biased meanings, images, language, and beliefs. Television contributes to this process by repeatedly presenting representations that children may internalize as ordinary social reality. Prior studies discussed in the source indicate associations between exposure, imitation, fear, aggression, and distorted perceptions, although they do not justify a single-cause explanation. Family mediation and media literacy can interrupt the process by helping children select, discuss, and evaluate content. The study recommends coordinated responsibility among regulators, legislatures, media industries, production partners, families, schools, and civil society to strengthen child-sensitive broadcasting and media literacy.